2004
DOI: 10.1007/s00134-004-2446-7
|View full text |Cite
|
Sign up to set email alerts
|

Static pressure-volume curve characteristics are moderate estimators of optimal airway pressures in a mathematical model of (primary/pulmonary) acute respiratory distress syndrome

Abstract: A recruitment maneuver followed by subsequent reduction in airway pressure limits end-expiratory atelectasis, overstretching, and pressure. None of the objective characteristics of the pressure-volume curve was predictive for end-expiratory atelectasis, overstretching, or optimal airway pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…22,[53][54][55][56][57][58][59] By doing so, less CDP is needed to maintain a certain lung volume on the inflation limb, because of the hysteresis of the respiratory system. In our view and practice, this can be achieved in clinical practice in patients with DAD by initially setting the CDP 3-5 cm H 2 O above the mean airway pressure on conventional mechanical ventilation, as the distal CDP is lower than the set proximal CDP.…”
Section: Best Hfov Approach and Oscillator Settings For Oxygenationmentioning
confidence: 99%
“…22,[53][54][55][56][57][58][59] By doing so, less CDP is needed to maintain a certain lung volume on the inflation limb, because of the hysteresis of the respiratory system. In our view and practice, this can be achieved in clinical practice in patients with DAD by initially setting the CDP 3-5 cm H 2 O above the mean airway pressure on conventional mechanical ventilation, as the distal CDP is lower than the set proximal CDP.…”
Section: Best Hfov Approach and Oscillator Settings For Oxygenationmentioning
confidence: 99%
“…Moreover, clinical studies using CT scans have revealed that the lung units' threshold pressures (TOP and TCP) obey a normal (Gaussian) distribution [21]. In the model, mean and SD of TOP and TCP pressures were given the values shown in Table II to simulate different intensities of ARDS [26]. The mean indicates the pressure at which the maximum of recruitment (TOP) and derecruitment (TCP) of lung units occurs, whereas SD describes the spread of the lung units' population with respect to the TOP and TCP.…”
Section: Eit-based Monitoring Of Ventilated Ards Patientsmentioning
confidence: 99%
“…These two states are governed only by the Threshold Opening Pressure (TOP) which the critical pressure above which the lung unit pops open and Threshold Closing Pressure (TCP) below which the unit collapses respectively. The model uses normally distributed TOP and TCP pressures with a specific mean and standard deviation [18] that may be adjusted to reflect the heterogeneous characteristic of alveoli under different abnormal lung conditions such as ARDS [19], [20]. Fig.…”
Section: A Model Of the Lung Mechanicsmentioning
confidence: 99%